Assessing Acquired Science Process Skills Of Senior High Schools In Central Region, Ghana - KOOMSON, ANTHONY (Advances in Social Sciences Research Journal, 2021)
Development and acquisition of science process skills (SPS) is necessary for understanding of science and offering of solutions to scientific problems. Assessing SPS acquired by students is key to monitor its development and acquisition. The study used descriptive survey to find out the nature of SPS developed and acquired by final year senior high school chemistry students. The study used parametric achievement test instrument called Students’ development of science process skills index Test. The test was conducted for 904 students drawn from 20 out of 36 Senior High Schools in the central region of Ghana, that offer elective science courses. The schools and students were sampled from 17 out of 20 districts in the central region of Ghana via multi-stage sampling technique taking into cognizance the school grades categories in Ghana comprising Grades A, B and C. The analysis of the result shows that students acquired mainly basic SPS like Observing, Communicating, and integrated SPS like Interpreting. However, SPS like Classifying, Hypothesising, Controlling Variables and Experimenting were hardly developed/acquired. The acquisition of SPS was also found to depend significantly on the type of school attended and gender. It is recommended that more opportunity be given to practice and access SPS, particularly, the integrated SPS.